High-strength wear-resistant fabric and preparation method thereof

By applying modified water-based polyurethane emulsion to the knitted fabric and introducing flame retardant modifiers and modification additives, the wear and flammability problems of the fabric in high-strength use environments are solved, and high-strength wear resistance and excellent flame retardant performance are achieved.

CN119593229APending Publication Date: 2025-03-11WILKIE TECHN TEXTILES JIAXING
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411961883.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing knitted fabrics are prone to wear in high-strength use environments, and have insufficient flammability and flame retardant properties, making it difficult to meet the growing demand for wear resistance, flame retardant and durability.

Method used

By applying the modified aqueous polyurethane emulsion onto the base cloth layer, a dense and uniform film is formed, and the mechanical properties, wear resistance and flame retardant properties of the fabric are improved.

Benefits of technology

The high-strength wear resistance and excellent flame retardant properties of the fabric are achieved, the durability and hydrophobicity of the fabric are enhanced, and the overall performance of the fabric is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217374690000101
    Figure BDA0005217374690000101
Patent Text Reader

Abstract

The invention relates to the field of wear-resistant fabrics, and discloses a high-strength wear-resistant fabric and a preparation method thereof.The high-strength wear-resistant fabric comprises a surface coating and a base cloth layer, the surface coating and the base cloth layer are formed by coating and drying modified waterborne polyurethane emulsion, and the modified waterborne polyurethane emulsion comprises isophorone diisocyanate, ethylene glycol terephthalate, 2, 3, 4-trimethyl-1, 3-pentanediol monoisobutyrate, polyisobutylene glycol monoisobutyrate, according to the present invention, 2, 2-dimethylolpropionic acid, a modified additive, a flame retardant modifier, 1, 4-butanediol, trimethylolpropane and the like are adopted to prepare the modified additive, dopamine is subjected to in-situ auto-polymerization on the surface of a titanium dioxide nanotube, nano-silica is grown on the surface in situ, and modification is performed through a polysiloxane solution to prepare the modified titanium dioxide nanotube flame retardant; the polysiloxane solution is prepared by carrying out a reaction on methyl triethoxysilane and dihydroxyl-terminated polydimethylsiloxane; the flame-retardant modifier is prepared by reacting 2-chloro-4, 6-diamino-1, 3, 5-triazine, 5-hydroxymethylfurfural and phosphorous acid, so that the fabric is endowed with good mechanical properties and wear resistance, and the fabric has a hydrophobic surface and is excellent in flame retardance and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wear-resistant fabrics, and in particular relates to a high-strength wear-resistant fabric and a preparation method thereof. Background Art

[0002] Knitted fabrics are soft, breathable, elastic, and easy to produce. Commonly used fabrics made of polyester, cotton, nylon, and core-spun yarn are comfortable to wear, fit well, and are not tight. Therefore, they are widely used in home furnishing, medical, and clothing. Wear-resistant fabrics are widely used in daily life, especially in clothing, bags, tents, and other occasions that need to withstand frequent friction. As people pay more and more attention to health and sports, daily clothing wear is gradually increasing, especially for some consumers who love fitness and outdoor sports, who have higher and higher requirements for the wear resistance of clothing fabrics.

[0003] The wear resistance of fabrics directly determines whether they can resist repeated friction from external objects without being easily damaged during use. If the wear resistance of fabrics is poor, they cannot resist wear for a long time in a high-intensity use environment, thereby reducing the service life of the product. The prior art usually introduces various wear-resistant fillers into knitted fabrics to prepare functional fabrics. However, due to the uneven dispersion of various wear-resistant fillers, they are easy to stack, resulting in poor corresponding functionality. In addition, existing knitted fabrics are easy to burn. The flammable characteristics of the fabrics cause serious fire hazards during use. With the increase in demand for use, the flame retardancy of fabrics has been put forward for durability. Commonly used flame retardants are water-soluble and cannot be permanently fixed on the surface of the fabric without the addition of additives, resulting in poor durability. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a high-strength wear-resistant fabric and a preparation method thereof, introduce a flame retardant modifier into the main chain of the waterborne polyurethane molecule, and add a modified additive to prepare a modified waterborne polyurethane emulsion, the waterborne polyurethane emulsion forms a dense and uniform film on the surface of the base fabric layer, giving the fabric good mechanical properties and wear resistance, and it has a hydrophobic surface, excellent flame retardant properties and durability.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-strength wear-resistant fabric, comprising a top coating layer and a base fabric layer formed by coating and drying a modified waterborne polyurethane emulsion, wherein the modified waterborne polyurethane emulsion comprises the following components in parts by weight: 17-25 parts of isophorone diisocyanate, 45-55 parts of ethylene terephthalate, 1.5-3 parts of 2,2-dimethylol propionic acid, 3-7 parts of a modifying additive, 15-30 parts of a diluent, 0.01-0.05 parts of dibutyltin dilaurate, 2-5 parts of a flame retardant modifier, 0.5-1.5 parts of 1,4-butanediol, 1-4 parts of trimethylolpropane, 2-6 parts of triethylamine, and 120-160 parts of deionized water;

[0007] The modified additive is prepared by in-situ self-polymerization of dopamine on the surface of titanium dioxide nanotubes to form coated titanium dioxide nanotubes, then in-situ growth of nano-silicon dioxide on the surface of the coated titanium dioxide nanotubes by a sol-gel method, and low surface energy modification by a polysiloxane solution, wherein the titanium dioxide nanotubes are prepared by a solvothermal method in a mixed solution of ethanol, glycerol and ether using titanyl sulfate as a precursor, and the polysiloxane solution is prepared by a sol-gel method using methyltriethoxysilane and dihydroxy-terminated polydimethylsiloxane for reaction;

[0008] The flame retardant modifier is prepared by using 2-chloro-4,6-diamino-1,3,5-triazine and 5-hydroxymethylfurfural to undergo a Schiff base reaction and then further undergo an addition reaction with phosphorous acid.

[0009] Preferably, the base fabric layer is one of pure cotton fabric, polyester-cotton fabric, polyester fabric, and nylon fabric; and the diluent is any one of dimethylacetamide, acetone, N,N-dimethylformamide, and N-methylpyrrolidone.

[0010] Preferably, the preparation method of the modified aqueous polyurethane emulsion comprises the following steps:

[0011] Weigh each raw material by weight, take ethylene terephthalate, 2,2-dimethylolpropionic acid and modifying additives into a reactor, add a diluent, stir and disperse evenly at 80-95°C, then cool to 70-85°C, add isophorone diisocyanate and dibutyltin dilaurate, react at a constant temperature for 4-6 hours, continue to cool to 55-65°C, add a flame retardant modifier to extend the chain for 0.5-1h, then add 1,4-butanediol and trimethylolpropane, extend the chain at a constant temperature for 1-2h, cool to 35-45°C, add a neutralizing agent triethylamine, neutralize at a constant temperature for 0.5-1h, cool to room temperature after the reaction is completed, add deionized water for emulsification under stirring, and prepare a modified waterborne polyurethane emulsion.

[0012] Preferably, the method for preparing the modified additive comprises the following steps;

[0013] (1) adding titanium sulfate to ethanol and stirring to disperse evenly, then adding propylene glycol and ether, stirring and dispersing for 10 to 12 hours to form a uniform solution, transferring the solution to an autoclave, placing it in an oven at 165 to 175° C. to heat and react for 8 to 12 hours, washing and drying the product after the reaction is completed, placing it in a quartz boat, and keeping it in a muffle furnace at 550 to 650° C. for 3 to 5 hours to prepare titanium dioxide nanotubes;

[0014] (2) ultrasonically dispersing titanium dioxide nanotubes in a Tris-HCl buffer solution with a pH value of 8.5 to obtain a dispersion, dissolving dopamine in deionized water, and slowly dropping it into the dispersion, stirring for 3 to 5 hours, and washing and drying after the reaction to obtain coated titanium dioxide nanotubes;

[0015] (3) taking methyltriethoxysilane, ethanol and deionized water into a reactor, adjusting the pH value of the solution to 2-3 with phytic acid, stirring and reacting at 14-17° C. for 20-30 min, then adding dihydroxy-terminated polydimethylsiloxane, heating to 55-70° C. and reacting for 0.5-1 h, to prepare a polysiloxane solution;

[0016] (4) The coated titanium dioxide nanotubes, anhydrous ethanol and ammonia water are placed in a reactor and dispersed uniformly by ultrasonication. Then, ethyl orthosilicate and polysiloxane solution are slowly added dropwise at 30-45° C. and stirred for reaction for 4-8 hours. After the reaction is completed, the modified additive is prepared by filtering, washing and drying.

[0017] Preferably, in step (1), the addition ratio of titanyl sulfate, ethanol, glycerol and ether is 1-1.3 g: 16-19 mL: 7-12 mL: 7-12 mL.

[0018] Preferably, in the step (3), the addition ratio of methyltriethoxysilane, ethanol, deionized water and dihydroxy-terminated polydimethylsiloxane is 12-14 g: 1-2 mL: 10-15 mL: 2.4-2.8 g.

[0019] Preferably, in step (4), the addition ratio of coated titanium dioxide nanotubes, anhydrous ethanol, ammonia water, tetraethyl orthosilicate and polysiloxane solution is 1-2 g: 40-85 mL: 2-5 mL: 4-9 mL: 0.5-2 mL.

[0020] Preferably, the preparation method of the flame retardant modifier comprises the following steps: taking 2-chloro-4,6-diamino-1,3,5-triazine and 5-hydroxymethylfurfural in a reactor, adding toluene solvent, placing it at 85-95°C and stirring the reaction for 6-8h, then adding phosphorous acid and continuing to stir the reaction for 4-6h, after the reaction is completed, removing the solvent by rotary evaporation, washing, filtering and drying to prepare the flame retardant modifier.

[0021] Preferably, the molar ratio of the 2-chloro-4,6-diamino-1,3,5-triazine, 5-hydroxymethylfurfural and phosphorous acid is 1:2-2.3:2-2.5.

[0022] The method for preparing the high-strength wear-resistant fabric as described above comprises the following steps:

[0023] S1, pretreating the base fabric layer with a 0.5-2% sodium hydroxide solution at 80-100° C. for 10-30 min, then washing with deionized water, and then drying the base fabric layer to a constant weight to obtain a pretreated base fabric layer;

[0024] S2. Immerse the pretreated base fabric layer in the modified aqueous polyurethane emulsion for 10 to 20 minutes, then take it out and put it into an oven at 60 to 80° C. to dry it to a constant weight, thereby preparing a high-strength wear-resistant fabric.

[0025] Beneficial effects of the present invention:

[0026] The invention uses titanyl sulfate as a precursor, and uses a solvothermal method in a mixed solution of ethanol, glycerol and ether to prepare a porous titanium dioxide nanotube with a large specific surface area, which has excellent mechanical, chemical and thermal durability properties. Then, dopamine is used to perform in-situ self-polymerization on the surface of the titanium dioxide nanotube to form polydopamine, and the titanium dioxide nanotube wrapped with polydopamine is used as a micro-nano building unit. Nano-silicon dioxide is in-situ grown on the surface of the coated titanium dioxide nanotube by a sol-gel method. The catechol and amino functional groups of dopamine can establish covalent and non-covalent interactions with the organic-inorganic surface, so that the polydopamine cross-linking layer is strongly adhered to the surface of the substrate, and a dense concave-convex micro-nano structure is formed, which strengthens the bonding between the nanoparticles and the titanium dioxide. The interface bonding strength between the nanotubes is improved, and a low surface energy modification is performed on the nanotubes through a polysiloxane solution to construct a hydrophobic surface, thereby preparing a modified additive, wherein the polysiloxane solution is prepared by a sol-gel method using methyltriethoxysilane and a dihydroxy-terminated polydimethylsiloxane to react. The introduction of the polysiloxane solution improves the dispersion uniformity of the nanoparticles, thereby improving the compatibility and density of the nanoparticles, making the wear surface smoother and denser, while the nano-silicon dioxide and titanium dioxide nanotubes improve the stiffness and load-bearing capacity of the surface coating, thereby improving the wear resistance of the fabric, and the polysiloxane can form a silicon-containing inorganic coating that is difficult to burn when heated, isolating the transmission of oxygen and combustible gases, and effectively improving the thermal stability and flame retardant properties of the fabric.

[0027] The invention utilizes the amino groups at both ends of 2-chloro-4,6-diamino-1,3,5-triazine and the aldehyde groups in the structure of 5-hydroxymethylfurfural to undergo Schiff base reaction to generate N=CH groups, which are then reacted with the PH bonds in the structure of phosphorous acid to prepare a flame retardant modifier containing nitrogen and phosphorus elements, thereby giving the fabric good flame retardant properties. The flame retardant modifier is then introduced into the molecular chain structure of waterborne polyurethane, the hard segment content of the polyurethane is increased, the intermolecular force is greatly improved, the wear resistance is improved, and better wear resistance is obtained. In addition, due to the addition of the flame retardant modifier, the cross-linking The degree of connection is improved, and the larger emulsion particle size forms a coating effect, which improves the wear resistance of the fabric. At the same time, the present invention uses sodium hydroxide solution to pretreat the base fabric layer, and then washes it with deionized water to remove impurities on the surface of the base fabric layer and improve hydrophilicity. Then, water-based polyurethane is used to form a dense and uniform film on the surface of the base fabric layer, connecting fibers and fibers, with excellent coating and density, and forming a strong chemical force between the flame retardant modifier and the fabric, so that the flame retardant modifier can be firmly fixed on the fabric and is not easy to fall off, thereby constructing a continuous and uniform durable flame retardant surface coating. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1 A method for preparing a modified additive comprises the following steps:

[0030] (1) 1 g of titanium oxysulfate was added to 18 mL of ethanol and stirred to disperse evenly, then 9 mL of propylene glycol and 9 mL of ether were added, and stirring and dispersing was continued for 12 h to form a uniform solution, the solution was transferred to an autoclave, and heated in an oven at 170 ° C for 10 h. After the reaction was completed, the product was washed and dried, and placed in a quartz boat, and kept at 600 ° C for 4 h in a muffle furnace to prepare titanium dioxide nanotubes;

[0031] (2) 1 g of titanium dioxide nanotubes were ultrasonically dispersed in 250 mL of Tris-HCl buffer solution with a pH value of 8.5 to obtain a dispersion, 0.5 g of dopamine was dissolved in 2 mL of deionized water, and then slowly added dropwise to the dispersion, stirred for reaction for 5 h, and after the reaction was completed, the coated titanium dioxide nanotubes were washed and dried to obtain;

[0032] (3) 12.3 g of methyltriethoxysilane, 1 mL of ethanol and 13 mL of deionized water were placed in a reactor, the pH value of the solution was adjusted to 3 using phytic acid, and the solution was stirred and reacted at 15° C. for 30 min, and then 2.5 g of dihydroxy-terminated polydimethylsiloxane was added, and the temperature was raised to 65° C. and reacted for 45 min to prepare a polysiloxane solution;

[0033] (4) 1 g of coated titanium dioxide nanotubes, 40 mL of anhydrous ethanol and 2 mL of ammonia water were placed in a reactor and dispersed evenly by ultrasonication. Then, 5 mL of tetraethyl orthosilicate and 0.7 mL of polysiloxane solution were slowly added dropwise at 40 °C and stirred for 6 h. After the reaction was completed, the modified additive was prepared by filtering, washing and drying.

[0034] Embodiment 2 A method for preparing a flame retardant modifier comprises the following steps:

[0035] 14.6 g of 2-chloro-4,6-diamino-1,3,5-triazine and 26.5 g of 5-hydroxymethylfurfural were placed in a reactor, 120 mL of toluene solvent was added, the mixture was stirred and reacted at 90 ° C for 8 h, and then 18.9 g of phosphorous acid was added and the stirring reaction was continued for 5 h. After the reaction was completed, the solvent was removed by rotary evaporation, and the flame retardant modifier was prepared after washing, filtering and drying.

[0036] Example 3 A modified aqueous polyurethane emulsion comprises the following components in parts by weight:

[0037] 17 parts of isophorone diisocyanate, 45 parts of ethylene terephthalate, 2 parts of 2,2-dihydroxymethylpropionic acid, 3 parts of the modified additive prepared in Example 1, 16 parts of diluent N-methylpyrrolidone, 0.02 parts of dibutyltin dilaurate, 2 parts of the flame retardant modifier prepared in Example 2, 0.5 parts of 1,4-butanediol, 2 parts of trimethylolpropane, 2 parts of triethylamine, and 120 parts of deionized water.

[0038] The preparation method of the modified aqueous polyurethane emulsion comprises the following steps:

[0039] Weigh each raw material by weight, take ethylene terephthalate, 2,2-dimethylolpropionic acid and modifying additives into a reactor, add a diluent, stir and disperse evenly at 85°C, then cool to 70°C, add isophorone diisocyanate and dibutyltin dilaurate, react at a constant temperature for 5 hours, continue to cool to 60°C, add a flame retardant modifier to extend the chain for 1 hour, then add 1,4-butanediol and trimethylolpropane, extend the chain at a constant temperature for 1.5 hours, cool to 40°C, add a neutralizing agent triethylamine, neutralize at a constant temperature for 0.5 hours, cool to room temperature after the reaction is completed, add deionized water for emulsification under stirring, and prepare a modified waterborne polyurethane emulsion.

[0040] A method for preparing a high-strength wear-resistant fabric comprises the following steps:

[0041] S1, pretreating the polyester-cotton fabric with a 1% sodium hydroxide solution at 85° C. for 25 minutes, then washing with deionized water, and then drying the polyester-cotton fabric to a constant weight to obtain a pretreated polyester-cotton fabric;

[0042] S2. Immerse the pretreated polyester-cotton fabric in the modified aqueous polyurethane emulsion for 15 minutes, then take it out and put it into an oven at 70° C. to dry it to a constant weight, thereby preparing a high-strength wear-resistant fabric.

[0043] Embodiment 4 A modified aqueous polyurethane emulsion comprises the following components in parts by weight:

[0044] 22 parts of isophorone diisocyanate, 50 parts of ethylene terephthalate, 2.5 parts of 2,2-dihydroxymethylpropionic acid, 5 parts of the modified additive prepared in Example 1, 24 parts of diluent N-methylpyrrolidone, 0.03 parts of dibutyltin dilaurate, 3 parts of the flame retardant modifier prepared in Example 2, 1 part of 1,4-butanediol, 3 parts of trimethylolpropane, 3 parts of triethylamine, and 137 parts of deionized water.

[0045] The preparation method of the modified aqueous polyurethane emulsion and the preparation method of a high-strength wear-resistant fabric are the same as those in Example 3.

[0046] Example 5 A modified aqueous polyurethane emulsion comprises the following components in parts by weight:

[0047] 24 parts of isophorone diisocyanate, 53 parts of ethylene terephthalate, 3 parts of 2,2-dimethylolpropionic acid, 6 parts of the modified additive prepared in Example 1, 28 parts of diluent N-methylpyrrolidone, 0.05 parts of dibutyltin dilaurate, 5 parts of the flame retardant modifier prepared in Example 2, 1,4-butanediol 1.5 parts, 4 parts of trimethylolpropane, 5 parts of triethylamine, and 149 parts of deionized water.

[0048] The preparation method of the modified aqueous polyurethane emulsion and the preparation method of a high-strength wear-resistant fabric are the same as those in Example 3.

[0049] Comparative Example 1 A modified aqueous polyurethane emulsion comprises the following components in parts by weight:

[0050] 24 parts of isophorone diisocyanate, 53 parts of ethylene terephthalate, 3 parts of 2,2-dihydroxymethylpropionic acid, 6 parts of titanium dioxide nanotubes prepared in Example 1, 28 parts of diluent N-methylpyrrolidone, 0.05 parts of dibutyltin dilaurate, 5 parts of flame retardant modifier prepared in Example 2, 1,4-butanediol 1.5 parts, 4 parts of trimethylolpropane, 5 parts of triethylamine, and 149 parts of deionized water.

[0051] The preparation method of the modified aqueous polyurethane emulsion comprises the following steps:

[0052] Weigh each raw material by weight, take ethylene terephthalate, 2,2-dimethylolpropionic acid and titanium dioxide nanotubes in a reactor, add a diluent, stir and disperse evenly at 85°C, then cool to 70°C, add isophorone diisocyanate and dibutyltin dilaurate, react at a constant temperature for 5 hours, continue to cool to 60°C, add a flame retardant modifier to extend the chain for 1 hour, then add 1,4-butanediol and trimethylolpropane, extend the chain at a constant temperature for 1.5 hours, cool to 40°C, add a neutralizing agent triethylamine, neutralize at a constant temperature for 0.5 hours, cool to room temperature after the reaction is completed, add deionized water for emulsification under stirring, and prepare a modified waterborne polyurethane emulsion.

[0053] The preparation method of a high-strength wear-resistant fabric is the same as that of Example 3.

[0054] Comparative Example 2 A modified aqueous polyurethane emulsion comprises the following components in parts by weight:

[0055] 24 parts of isophorone diisocyanate, 53 parts of ethylene terephthalate, 3 parts of 2,2-dihydroxymethylpropionic acid, 6 parts of the modified additive prepared in Example 1, 28 parts of diluent N-methylpyrrolidone, 0.05 parts of dibutyltin dilaurate, 1,4-butanediol 1.5 parts, 4 parts of trimethylolpropane, 5 parts of triethylamine, and 149 parts of deionized water.

[0056] The preparation method of the modified aqueous polyurethane emulsion comprises the following steps:

[0057] Weigh each raw material by weight, take ethylene terephthalate, 2,2-dihydroxymethylpropionic acid and modifying additives into a reactor, add a diluent, stir and disperse evenly at 85°C, then cool to 70°C, add isophorone diisocyanate and dibutyltin dilaurate, react at a constant temperature for 5 hours, continue to cool to 60°C, add 1,4-butanediol and trimethylolpropane, extend the chain at a constant temperature for 1.5 hours, cool to 40°C, add neutralizing agent triethylamine, neutralize at a constant temperature for 0.5 hours, cool to room temperature after the reaction is completed, add deionized water for emulsification under stirring, and prepare a modified waterborne polyurethane emulsion.

[0058] The preparation method of a high-strength wear-resistant fabric is the same as that of Example 3.

[0059] Performance Testing

[0060] The high-strength wear-resistant fabrics prepared in Examples 3-5 and Comparative Examples 1-2 were subjected to performance testing:

[0061] (1) Mechanical properties test: The mechanical properties of the samples were tested according to GB / T 3923.1-2013. The sample size was 25 cm × 5 cm and the tensile speed was 10 cm / min. The data results are shown in Table 1.

[0062] (2) Wear resistance test: According to GB / T 21196.1-2007, five parallel experiments were conducted and the test results were averaged. The data results are shown in Table 1.

[0063] (3) Flame retardant performance test: The limiting oxygen index value of the sample was tested by an oxygen index meter according to GB / T 5454-1997. The sample size was 12 cm × 5 cm. The data results are shown in Table 1.

[0064] (4) Washing resistance test: According to the standard conditions of AATCC 61-2006, the samples were placed in a water bath at 49°C (laundry detergent concentration: 0.15 w / v%) and washed for 45 min. The sample size was 12 cm × 5 cm. One wash was equivalent to 5 washes at home. The samples were then rinsed with clean water and dried at 60°C. The data results are shown in Table 1.

[0065] (5) Contact angle test: At room temperature, 5 μL of water was dropped onto the sample surface using a syringe to test the static water contact angle of the sample. Three different positions were randomly selected for each sample, and the average value was used to represent the contact angle of the sample. The data results are shown in Table 1.

[0066] Table 1 Sample performance test results

[0067]

[0068] From the data in Table 1, it can be seen that the fabrics prepared in Examples 3-5 of the present invention have excellent mechanical properties and wear resistance, the water contact angles are all greater than 120°, and they have hydrophobic surfaces, and their limiting oxygen index is high. After 20 washes, the limiting oxygen index can still reach 26.6-28.0%, and they have good flame retardant properties and durability. In Comparative Example 1, the modifying additive is replaced with titanium dioxide nanotubes in equal amounts, and the tensile strength, elongation at break, number of wear resistance, limiting oxygen index and water contact angle measured are lower than those of Examples 3-5, indicating that the addition of the modifying additive can improve the mechanical properties, wear resistance, flame retardant properties and hydrophobicity of the material. In Comparative Example 2, no flame retardant modifier is added, and the limiting oxygen index and number of wear resistance measured are significantly lower than those of Examples 3-5, indicating that the introduction of the flame retardant modifier can improve the flame retardant properties and wear resistance of the material.

[0069] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A high-strength wear-resistant fabric, characterized in that: The invention comprises a top coating layer and a base fabric layer formed by coating and drying a modified waterborne polyurethane emulsion, wherein the modified waterborne polyurethane emulsion comprises the following components in parts by weight: 17 to 25 parts of isophorone diisocyanate, 45 to 55 parts of ethylene glycol terephthalate, 1.5 to 3 parts of 2,2-dihydroxymethylpropionic acid, 3 to 7 parts of a modifying additive, 15 to 30 parts of a diluent, 0.01 to 0.05 parts of dibutyltin dilaurate, 2 to 5 parts of a flame retardant modifier, 0.5 to 1.5 parts of 1,4-butanediol, 1 to 4 parts of trimethylolpropane, 2 to 6 parts of triethylamine, and 120 to 160 parts of deionized water; The modified additive is prepared by in-situ self-polymerization of dopamine on the surface of titanium dioxide nanotubes to form coated titanium dioxide nanotubes, then in-situ growth of nano-silicon dioxide on the surface of the coated titanium dioxide nanotubes by a sol-gel method, and low surface energy modification by a polysiloxane solution, wherein the titanium dioxide nanotubes are prepared by a solvothermal method in a mixed solution of ethanol, glycerol and ether using titanyl sulfate as a precursor, and the polysiloxane solution is prepared by a sol-gel method using methyltriethoxysilane and dihydroxy-terminated polydimethylsiloxane for reaction; The flame retardant modifier is prepared by using 2-chloro-4,6-diamino-1,3,5-triazine and 5-hydroxymethylfurfural to undergo a Schiff base reaction and then further undergo an addition reaction with phosphorous acid.

2. The high-strength wear-resistant fabric according to claim 1, characterized in that: The base fabric layer is one of pure cotton fabric, polyester-cotton fabric, polyester fabric and nylon fabric; the diluent is any one of dimethylacetamide, acetone, N,N-dimethylformamide and N-methylpyrrolidone.

3. The high-strength wear-resistant fabric according to claim 1, characterized in that: The preparation method of the modified aqueous polyurethane emulsion comprises the following steps: Weigh each raw material by weight, take ethylene terephthalate, 2,2-dimethylolpropionic acid and modifying additives into a reactor, add a diluent, stir and disperse evenly at 80-95°C, then cool to 70-85°C, add isophorone diisocyanate and dibutyltin dilaurate, react at a constant temperature for 4-6 hours, continue to cool to 55-65°C, add a flame retardant modifier to extend the chain for 0.5-1h, then add 1,4-butanediol and trimethylolpropane, extend the chain at a constant temperature for 1-2h, cool to 35-45°C, add a neutralizing agent triethylamine, neutralize at a constant temperature for 0.5-1h, cool to room temperature after the reaction is completed, add deionized water for emulsification under stirring, and prepare a modified waterborne polyurethane emulsion.

4. The high-strength wear-resistant fabric according to claim 1, characterized in that: The preparation method of the modified additive comprises the following steps: (1) adding titanium sulfate to ethanol and stirring to disperse evenly, then adding propylene glycol and ether, stirring and dispersing for 10 to 12 hours to form a uniform solution, transferring the solution to an autoclave, placing it in an oven at 165 to 175° C. to heat and react for 8 to 12 hours, washing and drying the product after the reaction is completed, placing it in a quartz boat, and keeping it in a muffle furnace at 550 to 650° C. for 3 to 5 hours to prepare titanium dioxide nanotubes; (2) ultrasonically dispersing titanium dioxide nanotubes in a Tris-HCl buffer solution with a pH value of 8.5 to obtain a dispersion, dissolving dopamine in deionized water, and slowly dropping it into the dispersion, stirring for 3 to 5 hours, and washing and drying after the reaction to obtain coated titanium dioxide nanotubes; (3) taking methyltriethoxysilane, ethanol and deionized water into a reactor, adjusting the pH value of the solution to 2-3 with phytic acid, stirring and reacting at 14-17° C. for 20-30 min, then adding dihydroxy-terminated polydimethylsiloxane, heating to 55-70° C. and reacting for 0.5-1 h, to prepare a polysiloxane solution; (4) The coated titanium dioxide nanotubes, anhydrous ethanol and ammonia water are placed in a reactor and dispersed uniformly by ultrasonication. Then, ethyl orthosilicate and polysiloxane solution are slowly added dropwise at 30-45° C. and stirred for reaction for 4-8 hours. After the reaction is completed, the modified additive is prepared by filtering, washing and drying.

5. The high-strength wear-resistant fabric according to claim 4, characterized in that: In the step (1), the addition ratio of titanyl sulfate, ethanol, glycerol and ether is 1-1.3 g: 16-19 mL: 7-12 mL: 7-12 mL.

6. The high-strength wear-resistant fabric according to claim 4, characterized in that: In the step (3), the addition ratio of methyltriethoxysilane, ethanol, deionized water and dihydroxy-terminated polydimethylsiloxane is 12-14 g: 1-2 mL: 10-15 mL: 2.4-2.8 g.

7. The high-strength wear-resistant fabric according to claim 4, characterized in that: In the step (4), the addition ratio of the coated titanium dioxide nanotubes, anhydrous ethanol, ammonia water, tetraethyl orthosilicate and polysiloxane solution is 1-2 g: 40-85 mL: 2-5 mL: 4-9 mL: 0.5-2 mL.

8. The high-strength wear-resistant fabric according to claim 1, characterized in that: The preparation method of the flame retardant modifier comprises the following steps: taking 2-chloro-4,6-diamino-1,3,5-triazine and 5-hydroxymethylfurfural in a reactor, adding toluene solvent, stirring and reacting at 85-95°C for 6-8h, then adding phosphorous acid and continuing stirring and reacting for 4-6h, after the reaction is completed, removing the solvent by rotary evaporation, washing, filtering and drying to prepare the flame retardant modifier.

9. The high-strength wear-resistant fabric according to claim 8, characterized in that: The molar ratio of the 2-chloro-4,6-diamino-1,3,5-triazine, 5-hydroxymethylfurfural and phosphorous acid is 1:2-2.3:2-2.

5.

10. A method for preparing a high-strength wear-resistant fabric according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, pretreating the base fabric layer with a 0.5-2% sodium hydroxide solution at 80-100° C. for 10-30 min, then washing with deionized water, and then drying the base fabric layer to a constant weight to obtain a pretreated base fabric layer; S2. Immerse the pretreated base fabric layer in the modified aqueous polyurethane emulsion for 10 to 20 minutes, then take it out and put it into an oven at 60 to 80° C. to dry it to a constant weight, thereby preparing a high-strength wear-resistant fabric.

Citation Information

Cited By

  • Degradable environment-friendly packaging material and preparation method thereof

    CN120518991A

  • Modified TPU (thermoplastic polyurethane) base film for swelling adhesive tape and preparation method of modified TPU base film

    CN121006058A

  • High-air-permeability water-soluble composite non-woven fabric and preparation method thereof

    CN121556275A